“El Proceso” de Kafka desde la retórica - Pérez Márquez, Raquel (Foro Interno, 2007)
This article examines Franz Kafka’s The Trial using some of the keys to political thought offered by Javier Roiz and his teachers in the field of rhetoric. Kafka introduced the tragic genre in 20th century literature, reflecting the tensions of the modern citizen that is subject to political institutions that control the destinies and lives of individuals, entering in foro interno and leading to a loss of people’s capacity to judge freely. The masters of rhetoric observe that the formation of the State and citizens’ obedience to laws are two aspects of politics that have deeper philosophical roots than the Cartesian rationalism that dominates in Western Schools, and that the tension between Athens and Jerusalem, between truth and law, is in fact a more complex and richer source of thought.